A student-led clerkship primer: a near-peer orientation to clerkship - Zhao, Mars; Shirazi, Shayan; Trinder , Krista; Hominuke , Tamara; Ginger, Ruddy; Malin, Greg; McKague, Meredith (Canadian Medical Education Journal, 2023)
Implication Statement The transition between pre-clerkship and clerkship can be difficult for medical students. Near-peer teaching may fill knowledge gaps within curricular clerkship orientation, leveraging recent, relatable, and up-to-date experiences from near-peers. These benefits have not been formally evaluated in the context of a clerkship orientation. We therefore created the Clerkship Primer, a near-peer teaching initiative that aimed to introduce incoming clerks to clerkship through a curricular session facilitated exclusively by senior clerkship students. Sessions had high satisfaction among students. This pilot project suggests that curricular near-peer teaching is a valuable component of clerkship orientation.